On the moments of order statistics from discrete distributions - Çalik, Sinan; Güngör, Mehmet; Colak, Cemil (My University, 2010)
In this paper, the mth raw moments of order statistics from discrete distributions are obtained. By using the mth raw moments, a relation between the moments of sample maximum of order statistics from a discrete uniform distribution and the sum S (N-1, n) is obtained. It is shown that with the help of this relation, one can obtain all the moments for sample maximum of order statistics from a discrete uniform distribution. By using MATLAB, we compute the means and variances of the sample maximum order statistics for sample size N = 10(10)50(50)100 and n = 1(1)10. Further studies may focus on a software program computing the means and variances of sample maximum of order statistics from any discrete distributions. © 2010 Pakistan Journal of Statistics.
Keywords: Discrete distribution; Moment; Order statistics; Sum; Uniform distribution